BIOLOGICAL ASPECTS, CATCHING ASPECTS AND FISHING GROUND OF EASTERN LITTLE TUNA OR KAWAKAWA(Euthynnusaffinis (Cantor, 1849)) BASED ON THE FISHING GEAR AT WPP 572 - Gussasta Levi Arnenda; Bram Setyadji; Ngurah Intan Wiratmini; I Made Sara Wijana (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2020)
Eastern little tuna (Euthynnus affinis) is the main catch in WPP572. The caught E. affinis are still in their infancy. This research aims is to know the biological aspects, the fishing aspects and the distribution of the fishing gear per fishing gear, as a consideration for sustainable fisheries management. The research was carried out during the years 2019-2020. Taking samples for gonad observation was carried out by direct survey to the location in February, May, July and October 2019. The measurement of fish length was carried out in stratified random. Catching data were retrieved by requesting secondary data and interviews with related parties. The distribution of fishing grounds is mapped using the QGIS 3.4, the spatial distribution of catches is mapped. This study showed the size structure of E. affinis on purse seine, troll line and encircling gill netfishing gear from 16-55 cm FL, while on the boat/raft lift net it was 21-50 cmFL. These fish growth's is positive allometric on purse seine and encircling gillnet fishing gear, negative allometric on boat/raft lift net fishing gear, and isomeric on troll line. The sex ratio is in the ratio 1: 1.15 and balanced. Based on the maturity level, the gonads were mature in July and October and immature in February and May. Gonads ripened for the first time at a size of 42.032 cmFL. The distribution of the purse seine catchment areas at 3°-6°N and 93°-96°E, and 3°-6°S and 94°-95°E. Boat/raft lift net at 0°-3°S and 95° -101°E. Troll line 4°-6°N and 94°-95 E. Encircling gillnet 0°-2°S and 99°-101°E.